The Effect Of Wayground Application On Students' Vocabulary Mastery At The Tenth Grade Of SMA Negeri 1 Siempat Nempu Hulu - Agave Rumasdika Pasaribu; Harpen H.P Silitonga; Nenni Triana Sinaga (Lembaga Riset dan Inovasi Almatani, 2026)
Vocabulary mastery is a crucial component of English language learning; however, conventional vocabulary instruction often promotes passive learning and limited student engagement. Preliminary observations revealed that students demonstrated relatively low vocabulary mastery, indicating the need for more interactive digital learning tools. This study, therefore, aimed to examine the effect of the Wayground application on improving tenth-grade students’ vocabulary mastery and to compare the learning outcomes of students taught using Wayground with those instructed through conventional methods through a quantitative experimental approach employing a non-equivalent control group design involving two tenth-grade classes consisting of 60 students, using a 20-item multiple-choice vocabulary test administered through pre-test and post-test procedures. The findings revealed that although both groups experienced improvement, the experimental group demonstrated substantially greater progress, with the mean score increasing from 47 to 76 compared to the control group, which improved only from 48 to 51, while the Independent Samples t-test produced a value of 9.35 that exceeded the t-table value of 2.00 at the 0.05 significance level. These results indicate that the Wayground application significantly enhances students’ English vocabulary mastery and represents an effective digital learning tool for supporting vocabulary development in English language instruction.